A Rare Case of Vanishing Lung Syndrome - Sood, Nidhi (Hindawi Publishing Corporation, 2011)
We describe here a rare case of Idiopathic Bullous Emphysema/Vanishing Lung Syndrome (VLS) in a 33-year-old male patient with a history of marijuana abuse who presents to the hospital with pleuritic chest pain thought to be due to pneumothorax based on the chest radiograph. This case emphasizes the need to obtain chest computed tomography in a relatively stable patient suspected of VLS to reduce the potential risk of overseeing a bronchopleural fistula.